New insights into osmobiosis and chemobiosis in tardigrades - Hvidepil, Lykke K. B.; Møbjerg, Nadja (Frontiers in Physiology, 2023)
Tardigrades are renowned for their ability to enter the extremotolerant state of latent life known as cryptobiosis. While it is widely accepted that cryptobiosis can be induced by freezing (cryobiosis) and by desiccation (anhydrobiosis), the latter involving formation of a so-called tun, the exact mechanisms underlying the state—as well as the significance of other cryptobiosis inducing factors—remain ambiguous. Here, we focus on osmotic and chemical stress tolerance in the marine tidal tardigrade Echiniscoides sigismundi. We show that E. sigismundi enters the tun state following exposure to saturated seawater and upon exposure to locality seawater containing the mitochondrial uncoupler DNP. The latter experiments provide evidence of osmobiosis and chemobiosis, i.e., cryptobiosis induced by high levels of osmolytes and toxicants, respectively. A small decrease in survival was observed following simultaneous exposure to DNP and saturated seawater indicating that the tardigrades may not be entirely ametabolic while in the osmobiotic tun. The tardigrades easily handle exposure to ultrapure water, but hypo-osmotic shock impairs tun formation and when exposed to ultrapure water the tardigrades do not tolerate DNP, indicating that tolerance towards dilute solutions involves energy-consuming processes. We discuss our data in relation to earlier and more contemporary studies on cryptobiosis and we argue that osmobiosis should be defined as a state of cryptobiosis induced by high external osmotic pressure. Our investigation supports the hypothesis that the mechanisms underlying osmobiosis and anhydrobiosis are overlapping and that osmobiosis likely represents the evolutionary forerunner of cryptobiosis forms that involve body water deprivation.